Cardiotoxicity Effects of Herbal Medicine, A Review Article - Shahin Gavanji (Biology, Medicine, & Natural Product Chemistry, 2023)
With the development of human's modern society more and more people tend to use complementary and alternative medicine (CAM). Toxicological studies indicated that many herbal medicines have direct toxic effects on the circulatory system or cardiovascular system and cause harmful effects on the body. Cardiotoxicity or heart damage is a serious issue defined as heart electrophysiology dysfunction, affecting the cardiac structure, and muscle damage that arises from the drug or chemical poisoning agents, that may lead to heart failure. The aim of this review article is to provide various information about the potential adverse effects of herbal medicine on the cardiovascular system and introduce herbs that induced cardiac toxicity. To provide this review, all reported cases of cardiac toxicity induced by herbal medicines and natural products were collected through research articles and documents, and the most relevant articles, and books in various authentic search engines including Scopus, PubMed, SID (scientific information database), Science Direct and Google Scholar, from 1984 to April 2022 were searched, and selected herbs with therapeutic properties which induce toxic effects on the cardiovascular system are introduced. In this review, scientific data regarding cardiotoxicity showed that 16 herbs from 11 families may increase cardiac toxicity. Therefore, it's important to use herbal medicines and natural products under the guidance of medical professionals.